Multi-interpenetration driven ultra-robust ionic HOF with high proton conductivity for DMFCs - Bai, Xiang-Tian; Cao, Li-Hui; Yang, Yan; Chen, Xu-Yong (Chemical communications (Cambridge, England), 2024)
Herein, a novel ionic hydrogen-bonded organic framework (iHOF-12) was synthesized. The 5-fold interpenetrating network structure and charge-assisted synergistic effects enable iHOF-12 to maintain robustness under demanding conditions and attain excellent proton conductivity of 1.23 × 10 −2 S cm −1 , which contributes to the enhancement of the DMFC performance. 3D ultra-robust iHOF-12 exhibits 5-fold interpenetration and its inherent well-defined H-bond network imparts proton conductivity up to 10 −2 S cm −1 .